PELATIHAN PENGOLAHAN KACANG TANAH DI KELURAHAN PENATIH KECAMATAN DENPASAR TIMUR KOTAMADYA DENPASAR - Ina, P.T.; Ekawati, I.G.A.; Kencana Putra, I.N.; Widpradnyadewi, P.A.S.; Pratiwi, I.D.P.K. (Buletin Udayana Mengabdi; Vol 16 No 3 (2017), 2018)
Ratna Tani women farmers is a group of women farmers from Penatih which has a limited ability in processing peanut. The purpose of this activity was to enhance the ability and skill of KWT Ratna Tani in the processing of peanuts. Peanuts can be processed into atom peanut and milk peanut. Method of solving the problem of this activity is the practice of processing peanut products based on scientific studies and practice of packaging peanuts processed products in efforts to develop home industry of processed peanuts. One day training activities carried out on Thursday, August 4, 2016 of peanut processing technology into products peanuts and peanut milk atom. The success of this activity assessed on the participation of the participants during the extension through activity in the discussions, product processing practices and the presence of participants.